Contributions of the Fairy Tales to the Children on the Basis of the Teachers’ Views - Kabaday, Abdülkadir (American Journal of Education and Learning, 2019)
Having a worldwide association the aims of fairy tales are to preserve, promote, and develop this ancient teaching art. Fairy tales are also known as the magic atmosphere telling the reality indirectly and preparing the children for the future while nurturing and enriching their spirits. Thirty-two preschool teachers participated in this qualitative study via interview. The participants were required to respond the open-ended questions in written form. This study is conducted to analyze the characteristics of fairy tale books and the contributions of the tale telling to the children’s various domains such as cognitive, language, emotional, social, psycho- motor via teachers’ views. In this study, first, the definition and educational values of telling fairy tales was explained. Later, the data handled from the study were analyzed through content analysis technique and the findings were evaluated and interpreted. As a last remark, some recommendations were made to the teachers and parents about the choice of telling fairy tales. As a result of the evaluation, it was found out what fairy tales are popular among the children and that telling tale contributed children’s cognitive, moral, language, psycho-motor, social, personal, socio-emotional etc., domains.